Integrated assisted post (Posbindu) to lowering high prevalence of hypertension and diabetes mellitus - Susilawati, Tri Nugraha; Ismanta, Anestasia Darmastuti; Bernarda, Clarisca Calcafiorentina; Nandyantami, Farah Fauziah; Hilmy, Farhan; Basaria, Kevyn; Nazili, Muhammad Haqin; 'Ulwiyah, Nuuriyah; Zahida, Sarah; Nugraha, Yanika Tiara; Adiby, Zulfi Azam (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2024)
Introduction: Non-communicable diseases (NCDs) contribute to 74% of global mortality and are responsible for 73% of national casualties. It had been predicted that in 2024, the number of patients with NCDs in Indonesia will be around 92 million people, and among others, hypertension and diabetes mellitus (DM) are significant health burdens in this country. This paper presents a community service activity aimed at screening for NCDs in Sana Village, Sragen Regency, Central Java Province, Indonesia. Methods: An integrated assisted post (Posbindu)was held for early detection and to monitor the main risk factors of NCDs, particularly hypertension and DM. Fifty working-age adults from the Sana village were targeted to attend the Posbindu. Blood pressure and blood glucose levels were measured, followed by treatment and health counseling by the medical students, Mondokan health center officers, and local midwives. Results: The activity was well appreciated by the local community, with a participation rate of 226% (113 attendees out of 50 people targeted), consisting of 22 men and 91 women aged 22–93 years old. Hypertension and DM were detected in 61.9% (70/113) and 5.3% (6/113) participants. Conclusion: The high prevalence of NCDs, particularly hypertension, highlights the importance of maintaining physical fitness and carrying out health checks regularly. Thus, NCD screening through Posbindu is expected to be sustainable.